Analisis Performansi HTTP Networking Library pada Android (Studi Kasus: Portal Berita) - Mochammad Syaifullah Ferryansyah; Mahardeka Tri Ananta; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of technology that more sophisticated, making the news spread faster. Initially news is presented in conventional forms such as newspapers. Slowly the news is presented in the form of mobile apps. In its implementation, application developers use various libraries to create a news portal. The frequently used libraries include HttpURLConnection, Asynchronous Http Client, Retrofit, and OkHttp. But the performance of each library is unknown. Therefore, needs a research to provide performance information from each library. In this research, metrics are response time, memory usage, and network usage as a comparison between libraries. Testing consists of a comparison between text data and text data along with images. The results of this study showed that the fastest response time in OkHttp library with an average of 148,675 ms. The smallest usage memory in the HttpURLConnection library with an average of 13906.1 KB. While the smallest network usage on Asynchronous Http Client library with an average of 67196.5 B. The test results in this study also showed an increase in response time of each library when the accessed data is text and image data. And there is an increase in memory usage and network usage memory when the accessed data is text and image data.